Mechanical Strengthening of Lightweight Aluminium Alloys through Friction Stir Process - P. Yogesh; Santaji Krishna Shinde; Shyamlal. C; R. Suresh kumar; Moti Lal Rinawa; G. Puthilibai; M. Sudhakar; Kassu Negash; Rajesh S (Advances in Materials Science and Engineering)
The aerospace industries are focused on lightweighting with alloys having good tensile strength, fracture toughness, fatigue resistance, and corrosion resistance. The friction stir welding technology is one of the productive techniques in the aerospace industry to join such alloys with little ease. This paper deals with the composition of alloying elements that makes the structure lightweight and the impact of the precipitates evolved out of the selected alloying elements on the mechanical properties such as tensile strength and hardness of the joint in the aerospace alloys such as AA2xxx conventional aluminium alloys, AA2xxx lithium-based aluminium alloys, and AA7xxx aluminium alloys.